THE USE U-DICTIONARY TO INCREASING THE STUDENT’ VOCABULARY - Dewi Wulandari, Cici Handayani (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2020)
The lack of speaking competence is influenced by several factors. One of them is the English teachers haven’t used the modern media in teaching process which can motivate the students to learn English actively. The students of SMA Negeri 1 Sei Kepayang Kiri have low motivation in speaking English whether during the English learning proses or speaking in public. Therefore, the researcher conducted a study in which the researchers apply the use of U-Dictionary as a learning media to increase the students’ vocabulary in teaching speaking. U- Dictionary is one of English offline dictionary that can be downloaded by every student in every grade. It can be found at playstore, one of application in android phone. It is easy to use either to increase the vocabulary or to improve the ability in pronouncing English word because U- Dictionary not only provides the meaning of a word but also giving the spell of a word. With U-Dictionary, Everyone not only can translate words and short phrases, but also practice the skills in any language. U- Dictionary can be used as an effective learning media to increase the students’ vocabulary. From the main tab, everyone can quickly access short tests and mini games to practice any language wanted. By using U- Dictionary as a learning media in teaching speaking particularly increasing the vocabulary, the students’ vocabulary has increased significantly. Based on the pre-test result, it was showed that the students only master about fifty words for the four categories; noun, adjective, verb and adverb. It is not a good condition where the senior high schools students only master about fifty words. It is equal to primary students’ vocabulary. During the research, the students got many vocabularies at least one hundred new words based on the category; noun, adjective, verb and adverb